1990
DOI: 10.1161/01.cir.82.4.1449
|View full text |Cite
|
Sign up to set email alerts
|

Creation of anastomoses between an extracardiac artery and the coronary circulation. Proof that myocardial angiogenesis occurs and can provide nutritional blood flow to the myocardium.

Abstract: The purpose of this investigation was to determine whether blood vessels could develop de novo between an extracardiac artery and a collateral-dependent zone of the heart and to quantify the nutritive blood flow afforded by the new vessels. We also adapted the preparation so that angiogenically active agents could be chronically administered directly to the site of neovascularization in subsequent studies. To induce neovascularization between a systemic artery and the coronary circulation, the left internal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The release of angiogenic factors comes after myocardial injury, ischemia, inflammation, mechanical stress, and myocardial hemorrhage, all of which likely occur with VSTENT placement [Kantor 1999;Simons 2004]. A highly regulated sequence of events, from migration of capillary endothelial cells to lumen formation to finally formation of microvascular networks, typically takes at least 2 weeks to occur with measurable results [Unger 1990;Kohmoto 1996]. This corresponds very closely to our results, which demonstrate a marked increase in perfusion at 3 weeks.…”
Section: E748supporting
confidence: 85%
“…The release of angiogenic factors comes after myocardial injury, ischemia, inflammation, mechanical stress, and myocardial hemorrhage, all of which likely occur with VSTENT placement [Kantor 1999;Simons 2004]. A highly regulated sequence of events, from migration of capillary endothelial cells to lumen formation to finally formation of microvascular networks, typically takes at least 2 weeks to occur with measurable results [Unger 1990;Kohmoto 1996]. This corresponds very closely to our results, which demonstrate a marked increase in perfusion at 3 weeks.…”
Section: E748supporting
confidence: 85%
“…In a later study, they concluded that the extracardiac anastomoses were capable of providing significant support for the improvement of left ventricular function (Unger et al, 1993). This research highlights the therapeutic possibilities for controlled vascular development and angiogenesis (Unger et al, 1990). Such treatment, potentially, could both inhibit pathological vascular growth, and enhance the development of collateral arteries subsequent to myocardial ischemia (Kass et al, 1992).…”
Section: Clinical Applicationsmentioning
confidence: 92%
“…Whether the capillaries and arterioles that appear in canine cardiac tissue treated with FGF function as well as existing vessels is not clear; however, newly created arterioles and capillaries can function as perfusing vessels (16). The beneficial function of coronary collateral vessels in salvaging the myocardium from ischemia has been discussed in experimental animal models of coronary stenosis or obstruction (4) and in clinical studies of ischemic heart disease (2,4,(17)(18)(19)(20).…”
Section: And 6)mentioning
confidence: 99%